Risk factors for stroke and myocardial infarction in women in the United Kingdom as assessed in general practice: a case-control study. Issue 5 (May 1989) - Thompson, S G; Greenberg, G; Meade, T W
Abstract : Data available in the United Kingdom through the Medical Research Council's General Practice Research Framework were recorded in a study of 603 women aged 45-69 with confirmed diagnoses of stroke or myocardial infarction, each matched by age with two controls. Current cigarette smoking and a family history of myocardial infarction were both strongly associated with the risk of stroke and myocardial infarction, with relative risks of 2.47 (95% confidence interval 1.89 to 3.23) and 1.93 (95% confidence interval 1.52 to 2.44) respectively. The relative risks associated with past smoking decreased according to the length of time since stopping smoking. A family history of stroke was not significantly related to the risk of stroke or myocardial infarction. Single women had a lower risk of stroke and myocardial infarction than married women (relative risk 0.49), but parity, past use of oral contraceptives, and menopausal state were not significantly related to the risk of stroke and myocardial infarction in this study. Other characteristics that were identified as risk factors either for subsequent stroke or for myocardial infarction included not only hypertension, diabetes, and past histories of stroke and myocardial infarction, but also past histories of gynaecological cancer and of venous thrombosis. The association with venous thrombosis may indicate the importance of the haemostatic system in a common pathogenesis of venous thrombosis and myocardial infarction.